Acute metabolic effects of tonic‐clonic seizures. Issue 4 (22nd October 2019) - Nass, Robert D.; Zur, Berndt; Elger, Christian E.; Holdenrieder, Stefan; Surges, Rainer
Abstract: Objective: Tonic‐clonic seizures (TCS) lead to metabolic stress and changes in related blood markers. Such markers may indicate harmful conditions but can also help to identify TCS as a cause of transient loss of consciousness. In this study, we hypothesized that the alterations of circulating markers of metabolic stress depend on the clinical features of TCS. Methods: Ninety‐one adults undergoing video‐EEG monitoring participated in this prospective study. Electrolytes, renal parameters, creatine kinase (CK), prolactin (PRL), lactate, ammonia, glucose, and other parameters were measured at inclusion and different time points after TCS. Results: A total of 39 TCS were recorded in 32 patients (six generalized onset tonic‐clonic seizures in 6 and 33 focal to bilateral tonic‐clonic seizures in 26 patients). Shortly after TCS, mean lactate, ammonia, and PRL levels were significantly increased 8.7‐fold, 2.6‐fold, and 5.1‐fold, respectively, with levels of more than twofold above the upper limits of the normal (ULN) in 90%, 71%, and 70% of the TCS and returned to baseline levels within 2 hours. Only postictal lactate levels were significantly correlated with the total duration of the tonic‐clonic phase. In contrast, CK elevations above the ULN were found in three TCS ( 10%) only with a peak after 48 hours. Immediately after the TCS, hyperphosphatemia occurred in one third of the patients, whereas hypophosphatemia was observed in one third 2 hours later. TCS led to subtle but significant alterations of other electrolytes, creatinine, and uric acid, whereas glucose levels were moderately increased. Significance: Lactate is a robust metabolic marker of TCS with elevations found in 90% of cases within 30 minutes after seizure termination, whereas ammonia rises in 70%, similarly to PRL. Phosphate levels show an early increase and a decrease 2 hours after TCS in a third of patients. CK elevations are rare after video‐EEG‐documented TCS, challenging its value as a diagnostic marker.